Bio-sniffer (gas-phase biosensor) with secondary alcohol dehydrogenase (S-ADH) for determination of isopropanol in exhaled air as a potential volatile biomarker - Chien, Po-Jen; Suzuki, Takuma; Tsujii, Masato; Ye, Ming; Toma, Koji; Arakawa, Takahiro; Iwasaki, Yasuhiko; Mitsubayashi, Kohji (Biosensors & bioelectronics, 2017)
Exhaled breath analysis has attracted lots of researchers attention in the past decades due to its advantages such as its non-invasive property and the possibility of continuous monitoring. In addition, several volatile organic compounds in breath have been identified as biomarkers for some diseases. Particularly, studies have pointed out that concentration of isopropanol (IPA) in exhaled air might relate with certain illnesses such as liver disease, chronic obstructive pulmonary (COPD), and lung cancer. In this study, a highly sensitive and selective biochemical gas sensor (bio-sniffer) for the breath IPA concentration determination was constructed and optimized. This bio-sniffer measures the concentration of IPA according to the fluorescence intensity of oxidized nicotinamide adenine dinucleotide (NADH), which was produced by an enzymatic reaction of secondary alcohol dehydrogenase (S-ADH). The NADH detection system employed an UV–LED as the excitation light, and a highly sensitive photomultiplier tube (PMT) as a fluorescence intensity detector. A gas-sensing region was developed using an optical fiber probe equipped with a flow-cell and enzyme immobilized membrane, and connected to the NADH measurement system. The calibration range of the IPA bio-sniffer was confirmed from 1ppb to 9060ppb that was comparable to other IPA analysis methods. The results of the analysis of breath IPA concentration in healthy subjects using the bio-sniffer showed a mean concentration of 16.0ppb, which was similar to other studies. These results have demonstrated that this highly sensitive and selective bio-sniffer could be used to measure the IPA in exhaled air, and it is expected to apply for breath IPA research and investigation of biomarkers for clinical diagnosis. [Display omitted] •An isopropanol bio-sniffer based on secondary alcohol dehydrogenase.•The Bio-sniffer measured IPA gas using the fluorescence intensity of NADH.•This IPA bio-sniffer possessed wide calibration range and high sensitivity.•Breath samples from healthy volunteers were measured by the IPA bio-sniffer.